2019
DOI: 10.3390/diagnostics9040193
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Asymmetry during Cognitive Tasks and Its Relationship with Suicide Ideation in Major Depressive Disorder: An fNIRS Study

Abstract: Reduced oxygenation changes in the prefrontal cortex during cognitive tasks have been reported in major depressive disorder (MDD). However, prefrontal asymmetry during cognitive tasks and its relation to suicide ideations have been less frequently examined in patients with MDD. This study investigated prefrontal asymmetry and its moderating effect on the relationship between depression severity and suicidal ideation in MDD patients during cognitive tasks. Forty-two patients with MDD and 64 healthy controls (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…According to the World Health Organization, the worldwide prevalence of depression is approximately 3%-5% (approximately 100 to 200 million people) [1]. By 2022, depression will become the most serious disease burden in developing countries, and major depressive disorder (MDD) will become the second leading cause of suicide and disease [2], [3]. Due to the lack of specific diagnostic methods for depression and its various manifestations, accurate and reliable diagnosis of depression mainly depends on the clinical skills and clinical judgment of psychologists [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization, the worldwide prevalence of depression is approximately 3%-5% (approximately 100 to 200 million people) [1]. By 2022, depression will become the most serious disease burden in developing countries, and major depressive disorder (MDD) will become the second leading cause of suicide and disease [2], [3]. Due to the lack of specific diagnostic methods for depression and its various manifestations, accurate and reliable diagnosis of depression mainly depends on the clinical skills and clinical judgment of psychologists [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a significant amount of research on MDD based on fNIRS has been widely performed, and these studies have shown the great potential of neural-signal-based MDD recognition [2], [17]. A recent analysis assessing depression pre-and post-treatment showed a consistent wave pattern, which led to the response in the frontal cortex being regarded as a trait marker [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic responses in the right middle frontal gyrus were also negatively correlated with aggression and hopelessness in the SAs but not in the HCs and NAs. Such negative correlation was corroborated by Baik et al (38), who also showed that MDD patients have relatively reduced left prefrontal oxy-Hb changes during VFT than HCs, and amongst the MDD patients, there was significant positive correlation between asymmetry index for VFT and the suicide item of HAM-D. With relatively greater left prefrontal asymmetry, the effect of depression severity on suicide ideation was also noted to be stronger. Additionally, Pu et al (41) also noted that regional hemodynamic changes in the right dorsolateral prefrontal cortex (DLPFC), orbitofrontal cortex (OFC), and right frontopolar cortex (FPC) regions in patients with MDD with suicidal ideation were significantly smaller than those without suicidal ideation, and similar differences were also noted between patients with MDDs and HCs.…”
Section: Correlation Of Fnirs Signals With Suicidalitymentioning
confidence: 55%
“…Although a significant positive correlation was shown between STAI-defined trait and state anxiety scores at resting conditions, the lateralized PFC activity during the arithmetic task performance in the present study was associated with state anxiety levels, but not with trait anxiety levels. On the other hand, MDD patients had reduced left PFC activity during verbal fluency tasks (VFT) [34] and emotionally challenging tasks [15]. The left PFC activity in MDD patients was reduced during cognitive or emotional tasks by impairing the downregulation of amygdala responses to negative emotional information [35].…”
Section: Discussionmentioning
confidence: 99%